In vitro study of difference fungicides in controlling rhizoctonia solani causal agent for sheath blight disease of rice / Amir Mohammed Taqiudin Mohd Zamberi - Mohd Zamberi, Amir Mohammed Taqiudin (Faculty of Plantation and Agrotechnology, 2019)
Rice (Oryza sativa L) is among the important cereal crop in the world and also a staple food for the most Asian country including Malaysia. Rice productivity must be enhanced in order to meet the increasing global demand and consumption. However, it is difficult to achieve the objective when the rice production need to face some limitation such as pest, disease, climate change and soil fertility. Disease is a major problem face by rice cultivators that could reducing their production of rice. Sheath blight disease of rice caused by Rhizoctonia solani was among the disease that cause serious threat on rice producing country all over the world. Various methods were used to solve this problem such as using the planting resistance varieties. However, the resistance gene not been found and most of the farmers was relied on chemical method to control this problem. The objective of this study were to evaluate the efficacy of difference fungicides in controlling sheath blight pathogen Rhizoctonia solani and to determine the effectiveness for difference concentration of difference fungicides in controlling sheath blight pathogen. This study was done by conducting in-vitro study of 4 difference fungicides with 2 difference concentration (0.2 ml and 2 ml) by using poisoned food technique. Fungicides that were used in this study was Amolin (difenoconazole 14.6% & Propiconazole 14.6%), Amotan (Azoxystrobin 22.8%), Myzim (carbendezim 34.0%), Fillia (Propiconazole 10.7% & tricyclazole 34.2 %). The mycelium inhibition growth was measured in order to identify which fungicides were effective in controlling R.solani under in vitro condition. Myzim (carbendezim 34.0%) was found to be the most effective fungicide with 95.88 percent mean mycelium inhibition percentage and the least effective fungicide is Amotan (Azoxystrobin 22.8%) with the mean mycelium inhibition growth 64.54 percent.